2001
DOI: 10.1111/1468-5965.00332
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Output and Inflation: Policy Conflicts and Co‐operation under a Stability Pact

Abstract: The article analyses in a simple setting a game between an inflationconservative central bank and a fiscal authority subject to an upper limit on the budget deficit. It is shown that complementarity or substitutability between the policies and the preference of each authority for the other authority's behaviour crucially depends on the type of shock hitting the economy. If the government attempts to stimulate output beyond its natural level, a 'deficit bias' emerges under non-co-operation; under co-operation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 35 publications
4
63
0
3
Order By: Relevance
“…Within the AS regime, government spending increases (relatively) with negative output fluctuations (and vice versa), which is how automatic stabilization has often been modelled previously (see e.g. Taylor, 2000;Artis and Buti, 2000;or Buti et al, 2001). In order to make this rule comparable to the DB, we assume that, in the steady-state, both rules are tied to steady-state revenues (which implies thatΨ P is regarded as a fixed constant in the AS regime).…”
Section: The Debt Brake (Db) and Additional Rule-based Stabilization mentioning
confidence: 60%
“…Within the AS regime, government spending increases (relatively) with negative output fluctuations (and vice versa), which is how automatic stabilization has often been modelled previously (see e.g. Taylor, 2000;Artis and Buti, 2000;or Buti et al, 2001). In order to make this rule comparable to the DB, we assume that, in the steady-state, both rules are tied to steady-state revenues (which implies thatΨ P is regarded as a fixed constant in the AS regime).…”
Section: The Debt Brake (Db) and Additional Rule-based Stabilization mentioning
confidence: 60%
“…The range of simulations revealed that the nature of the shocks affects the nature of the optimal policy response (Buti et al 2001). The shocks can affect quantities, prices, technology or the government revenues directly.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, some of these instruments can be employed independently by national governments while others require or imply varying degrees of policy coordination especially in a monetary union (Beetsma et al 2001, Buti et al 2001, Dixit et al 2001, Hughes Hallett et al 2001, Belke 2002, Gatti et al 2002, PisaniFerry 2002, Brück et al 2003. The term "coordination" in this article implies an inter-governmental agreement on the limitation of fiscal sovereignty supervised by the EC, not an explicit agreement between the fiscal and monetary authorities of the eurozone.…”
Section: Fiscal Policy In a Monetary Unionmentioning
confidence: 98%
“…Allowing for this possibility would not alter the conclusions of the model. 14 In models of EMU fiscal policy it is sometimes claimed that national governments are not concerned with the inflation rate, whose control is under the exclusive responsibility of the central bank (Buti et al 2001). None of our exogenous.…”
Section: The Fiscal Policy Problem Under Discretionmentioning
confidence: 99%